Dynamic Response of Al2024 T3 Aluminium Plate Subjected to Oblique Impact of 9mm Bullet Using Single Processor - Ibrahim, Mohd Norihan; Zakaria, Muhammad Ammar Imran (Research Progress in Mechanical and Manufacturing Engineering, 2020)
The design of armor as protection against weapons have started as earlier century and have been kept evolving ever since. In the modern world, the armor is essential to use as protective clothing against a direct contact weapon which mostly used in the military. The objective of this research is to evaluate the dynamic response of Al 2024 T3 aluminium target plate impacted by a small arms 9 mm bullet at different orientation angle and velocity range. In this study, the variations of impact velocity are 300 m/s, 400m/s, 500m/s and 600m/s while the orientation considered are 0°, 30° and 60°. The impact of the bullet on a plate will be evaluated by using ANSYS explicit finite element code in which 2 mm thickness of the target plate is considered as a deformable body. Upon completion of this study, various profiles failure of impact were observed and achieved. It was found that the range of impact speed and different orientations of bullet impact was significantly affecting the profile of failure of the impacted target plate. The impact velocity at the speed of 600 m/s with 30° orientations shows large deformation and penetration of impacted Al2024 T3 target plate while at the speed 600 m/s and 60° orientation indicate large deformation and deviation on the direction of post-impact motion of the bullet.